Le fonti e le tematiche teologiche della Regula di Eugippio - Degórski, Bazyli (Vox Patrum, 2020)
The article demonstrates and discusses the following sources of Eugippius’ Rule: St. Augustine of Hippo (Ordo monasterii and Praeceptum); Rules: Regula quattuor Patrum and Regula Magistri; St. Basil the Great (Regula [a Rufino latine versa]); St. Pachomius the Great (Regula); Novatus Catholicus (Sententia de humilitate et oboedientia et de calcanda superbia); St. John Cassian (Conlationes Patrum and the De institutis coenobiorum); St. Jerome (Epistula 125, 9). In its second part, the article discusses the theological subject matter of the Regula of Eugippius, also pointing out the relevance of its message to both his times and our own.